RESPONSE TO THE PROHIBITION OF ZAKAT (TITHE) COLLECTION BY PRIVATE ORGANIZATIONS IN ACEH, INDONESIA - Dodik Siswantoro (P3M STAIN Kudus, 2014)
Purpose – This paper aims to analyze the response to the prohibition on zakat (tithe) collection by private organizations in Aceh Indonesia. Qanun (Islamic regional law) No. 10/2007 explicitly prohibited private zakat organizations (Lembaga Amil Zakat (LAZ)) from collecting zakat as it is included in the government budget. However, there is no sanction for incompliance and private zakat organizations seek other funds for their activities. Design/Methodology/Approach – This paper is based on primary data from interviews in June 2013. Three private LAZs were interviewed on this specific case. Findings – This paper gives facts that each LAZ responded differently to the regulation. They still conduct the social activities without taking zakat as their source of funds. Practical Implications – This regulation caused uncertainty for LAZ; besides, they have to avoid what is prohibited in the regulation. However, this condition created some creativities of LAZ in order to survive and to service the community by promoting good programs. Originality/Value – This may be claimed as the first research on the area of prohibition on zakat (tithe) collection in Aceh Indonesia.